DAMPAK PARTISIPASI GURU DALAM PROGRAM KELUARGA BERENCANA TERHADAP PENGATURAN KELAHIRAN Darni Fakultas Bahasa dan Seni Universitas Negeri Surabaya, darniunesa@gmal.com (Lentera, Jurnal Studi Perempuan, 2014)
Abstract: The aim of this research is to find out teacher’s knowledge on family planning,  their  participation,  and  the  impact  of  that  knowledge  to  the  birth control.  This  research  is  quantitative  research.  The  sources  of  data  are teachers  (both  males  and  females)  in  Surabaya  region;  starting  from elementary  school,  Junior  high  school,  Senior  high  school,  and  Vocational school.  The  data  collection  used  questioner.  The  question  is  given  in  the  written form. The respondents write the feed-back closely and privately. The data analysis used  percentage  descriptive  statistic  analysis.  The  result  shows  that  teachers  and their partner who are mostly come from educated background have the awareness, conscious,  and  active  role  in  the  family  planning  programs.  It  is  shown  by  the number  of  their  children.  Most  of  them  only  have  two  children.  Uniquely,  the knowledge about family planning is not always obtained from counseling. They quite often search the information through media, audio visual, and pamphlets. More than 90% of teachers say that KB (family planning program) can control the birth rate. The aim of following KB program and using contraception is to control birth rate. By joining KB program, teachers can escalate their prosperity and the happiness of the family. Keywords: educated background, two children, contraception, the family’s prosperity